Age-related Clinical Features in Ischemic Colitis - Kurumada, Tomoyuki; Kohda, Katsuaki; Miwa, Takeshi; Deguchi, Ryuzou; Machida, Miho; Hasebe, Tetsunori (Nihon Rōnen Igakkai zasshi, 2000)
Ischemic colitis has been considered to have relatively high prevalence in the elderly population with underlying vascular disorder such as hypertension. However, this disease has been recently reported increased in the young population so that it is not necessarily limited to the aged. The aim of the present study was to elucidate the characteristics of age-related clinical features in ischemic colitis. The subjects consisted of 30 patients with ischemic colitis admitted to our hospital during the last 5 years. They were divided into the aged group more than 65 years old and the young group aged 65 or less. As a result, there were no significant differences in symptoms, resulted serological examination, endoscopic findings, and treatment period. Lesion sites were more extended in the aged group. Concerning underlying disease and etiologic factors, the vascular factor was important in the aged group, while the peristaltic factor, especially constipation was important in the young group. Ten of the 30 patients had habitual constipation, and the aged group had a high percentage of paralytic constipation, while the young group had a high rate of spastic constipation. Many patients with paralytic constipation had a history of underlying diseases and laparotomy, while the patients with spastic constipation did not have such a history. Therefore, it is presumed that the spastic type of constipation is an etiologic factor in ischemic colitis.